Application of Cat’s Whiskers (Orthosiphon aristatus ) Leaf Extract in Tambaqui (Colossoma macropomum) Infected with Aeromonas hydrophila - Marlinda, Marlinda; Dewi, Cut Dara; Putra, Dedi Fazriansyah (College of Vocational Studies, Bogor Agricultural University, 2025)
Treatment using environmentally friendly natural materials, such as Orthosiphon aristatus (cat’s whiskers) leaf extract, can inhibit the growth of Aeromonas hydrophila in Tambaqui juvenile (Colossoma macropomum). This study aimed to determine the effect of Orthosiphon aristatus leaf extract on Tambaqui juvenile infected with Aeromonas hydrophila and to identify the optimal concentration based on blood profile responses during treatment. The research was conducted from April to May 2024 at the Fish Hatchery and Breeding Laboratory, Faculty of Marine and Fisheries, Universitas Syiah Kuala. A Completely Randomized Design (CRD) was used, consisting of five treatments and four replications. The extract concentrations were as follows: Treatment A (control), B (2 ppt), C (3 ppt), D (4 ppt), and E (5 ppt), administered via immersion. The clinical symptoms observed after treatment indicated that the extract had a positive effect on the fish: they regained active swimming behavior, feeding response improved, red patches faded, mucus secretion decreased, and scales returned to normal. Abdominal swelling subsided, and eye conditions normalized. ANOVA results showed a significant difference in survival rate (P<0.05), with the highest survival observed in Treatment D (4 ppt), at 86.75 ± 5.31%. In conclusion, Orthosiphon aristatus leaf extract at a concentration of 4 ppt provided the best outcomes in terms of clinical symptoms, survival rate, leukocyte and erythrocyte counts, and hemoglobin levels, indicating its potential as an antibacterial agent for Tambaqui juvenile.